2008
DOI: 10.1007/s00264-008-0666-0
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception in total, hemi- and reverse shoulder arthroplasty in 3D motion analyses: a prospective study

Abstract: The aim of the study was to assess proprioception after shoulder arthroplasty. Twenty-six patients were enrolled who underwent total shoulder arthroplasty (TSA) (n=13) or hemi-arthroplasty (n=8) for shoulder osteoarthritis or reversed arthroplasty (n=5) for cuff tear arthropathy. All patients were examined before the operation and then again six months thereafter in a motion analysis study with an active angle-reproduction (AAR) test. In all groups the AAR deteriorated at 60°flexion (from 5.5°[SD 2.8] to 7.6°[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 15 publications
2
48
0
Order By: Relevance
“…Due to this, many groups call for this anatomy to be repaired as precisely as possible when implanting a humeral prosthesis in order to achieve optimal postoperative joint function [1,4,5,7,8,10,13,15,16,18,20,22,23]. Others go further and insist on reconstruction of the centre of rotation specifically [17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, many groups call for this anatomy to be repaired as precisely as possible when implanting a humeral prosthesis in order to achieve optimal postoperative joint function [1,4,5,7,8,10,13,15,16,18,20,22,23]. Others go further and insist on reconstruction of the centre of rotation specifically [17].…”
Section: Introductionmentioning
confidence: 99%
“…Different solutions have been proposed to prevent notching: Frankle et al suggested lateralising the centre of rotation outside the scapula, using an eccentric glenosphere that approaches two thirds of a sphere volume instead the one half used in the original Delta concept, creating more constraint and torque on the glenosphere and increasing the risk of glenoid loosening. Increasing the inclination (neck-shaft angle) of the humeral component will avoid inferior scapular notching [27], but then may create a superior conflict and enhance prosthetic loosening. Baulot and co-workers propose a new glenoid design manufactured by Aston Medical (Duocentric®) with extended inferior coverage that provoked no notching in a case series of 50 patients (unpublished data).…”
mentioning
confidence: 99%
“…However, to date there are only three studies analyzing proprioception after shoulder replacement [6,12,16]. Two of these studies [6,12] have a short follow-up period, in both cases six months.…”
Section: Proprioception After Shoulder Arthroplastymentioning
confidence: 99%
“…However, to date there are only three studies analyzing proprioception after shoulder replacement [6,12,16]. Two of these studies [6,12] have a short follow-up period, in both cases six months. Cuomo et al [6] performed a passive and guided angle-reproduction test in 20 patients with shoulder osteoarthritis before and six months after total shoulder arthroplasty (TSA) with only one degree of freedom at a time and reported improvement of proprioception [6].…”
Section: Proprioception After Shoulder Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation